Economic constrained optimization for power balancing in a DC microgrid: A multi-source elevator system application. (June 2020) - Pham, Thanh Hung; Prodan, Ionela; Genon-Catalot, Denis; Lefèvre, Laurent
Highlights: DC microgrid modeling using Port-Hamiltonian formulations on graphs. Electricity cost minimization using Economic Model Predictive Control. Simulations and comparisons validated on an elevator DC microgrid architecture. Abstract: This paper considers a discrete-time scheduling method for the power balancing of a continuous-time DC microgrid system. A high-order dynamics and a resistor network are used for modelling the electrical storage unit and the DC bus of the centralized microgrid system, respectively. A PH (Port-Hamiltonian) formulation on graphs is employed to explicitly describe the microgrid topology. This modelling approach allows us to derive a discrete-time model which preserves the power and energy balance of the physical system. Next, a constrained economic MPC (Model Predictive Control) using the proposed control model is formulated for efficiently managing the microgrid operation. The systematic combination of the network modelling method and optimization-based control allows us to generate the appropriate power profiles. Finally, the benefits of the proposed approach are validated through simulation and comparison results over a particular DC microgrid elevator system under different scenarios and using real numerical data.